A Normative Review of Indonesia's Tax Amnesty Law from an Islamic Constitutional Perspective - Alila Zahira Kusuma; Paisol Burlian; Eti Yusnita (STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
Tax amnesty remains one of the most debated fiscal policies in contemporary governance, particularly in Muslim-majority countries where legal legitimacy is expected to align with ethical and religious values. Existing studies primarily evaluate tax amnesty from economic, fiscal, and administrative perspectives, while limited attention has been given to its constitutional-ethical legitimacy within the framework of Islamic constitutionalism. This study aims to examine the normative legitimacy of Indonesia’s Tax Amnesty Law (Law No. 11 of 2016) through the principles of justice (al-?adl), public trust (am?nah), equality before the law (al-mus?w?h), and public welfare (ma?la?ah ??mmah). Employing normative juridical research with statutory, conceptual, and comparative approaches, the study analyzes legislation, Constitutional Court decisions, and contemporary literature on Islamic constitutional law and maq??id al-shar??ah. The findings reveal that although the tax amnesty policy achieved short-term fiscal objectives, it generated normative tensions concerning distributive justice, legal equality, and ethical accountability. Comparative evidence from Malaysia and Pakistan indicates that the integration of moral and religious narratives can enhance the legitimacy and public acceptance of fiscal policies. This study contributes to the literature by proposing an Islamic constitutional framework for evaluating fiscal legislation, integrating constitutional legality with moral legitimacy as a foundation for sustainable fiscal governance in Muslim-majority constitutional democracies. [Pengampunan pajak merupakan salah satu kebijakan fiskal yang paling diperdebatkan dalam tata kelola pemerintahan kontemporer, terutama di negara-negara mayoritas Muslim yang menuntut keselarasan antara legalitas hukum dengan nilai-nilai etika dan agama. Penelitian terdahulu umumnya menilai kebijakan pengampunan pajak dari perspektif ekonomi, fiskal, dan administrasi, sementara kajian mengenai legitimasi konstitusional-etis dalam kerangka hukum tata negara Islam masih relatif terbatas. Penelitian ini bertujuan menganalisis legitimasi normatif Undang-Undang Nomor 11 Tahun 2016 tentang Pengampunan Pajak berdasarkan prinsip keadilan (al-?adl), amanah, persamaan di hadapan hukum (al-mus?w?h), dan kemaslahatan umum (ma?la?ah ??mmah). Penelitian menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif melalui analisis terhadap peraturan perundang-undangan, putusan Mahkamah Konstitusi, serta literatur kontemporer mengenai hukum tata negara Islam dan maq??id al-shar??ah. Hasil penelitian menunjukkan bahwa meskipun kebijakan pengampunan pajak berhasil mencapai tujuan fiskal jangka pendek, kebijakan tersebut menimbulkan persoalan normatif terkait keadilan distributif, kesetaraan hukum, dan akuntabilitas etis. Analisis perbandingan dengan Malaysia dan Pakistan menunjukkan bahwa integrasi narasi moral dan nilai-nilai keagamaan dapat memperkuat legitimasi serta penerimaan publik terhadap kebijakan fiskal. Kontribusi penelitian ini adalah menawarkan kerangka evaluasi hukum fiskal berbasis konstitusionalisme Islam yang mengintegrasikan legalitas konstitusional dengan legitimasi moral sebagai fondasi tata kelola fiskal yang berkelanjutan dalam negara demokrasi konstitusional mayoritas Muslim.]